2024
DOI: 10.3389/fmed.2023.1279100
|View full text |Cite
|
Sign up to set email alerts
|

Stable closure of acute and chronic wounds and pressure ulcers and control of draining fistulas from osteomyelitis in persons with spinal cord injuries: non-interventional study of MPPT passive immunotherapy delivered via telemedicine in community care

Jeanette Sams-Dodd,
Maurizio Belci,
Surendra Bandi
et al.

Abstract: BackgroundMicropore particle technology (MPPT) is a topical wound treatment. It is a passive immunotherapy, acting via the skin and wound microbiome without the use of antimicrobial action. In a general patient population, it removed wound infections 60% and initiated tissue regeneration 50% quicker than antibiotics and antiseptics. As MPPT supports the immune system, the aim was to confirm that MPPT is also effective in immunocompromised individuals. People with spinal cord injury (SCI) are immunodeficient du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…In conclusion, the survey findings are in agreement with previous clinical evaluations of MPPT in persons with SCI ( 26 , 32 , 33 ). Respondents were overall highly positive towards MPPT and found that MPPT improved their quality-of-life.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In conclusion, the survey findings are in agreement with previous clinical evaluations of MPPT in persons with SCI ( 26 , 32 , 33 ). Respondents were overall highly positive towards MPPT and found that MPPT improved their quality-of-life.…”
Section: Discussionsupporting
confidence: 90%
“…This represents real-world-evidence provided by patients without the involvement of healthcare professionals and adds a new dimension to clinical studies ( 34 – 39 ). A comparison of this patient-reported outcome study and the non-interventional study with MPPT ( 33 ) finds that they both reported almost identical outcomes of treatment, i.e., 100% closure rates for acute and chronic pressure ulcers and control of soft tissue infection caused by osteomyelitis. They also both found that MPPT is suitable for self-care with the survey reporting that 83% of the respondents did not depend upon nurse support for treating their wounds or draining fistulas.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation